Existence of three positive solutions to some p-Laplacian boundary value problems - Sidi Ammi, M. R. (2014)
We obtain, by using the Leggett-Williams fixed point theorem, sufficient conditions that ensure the existence of at least three positive solutions to some p-Laplacian boundary value problems on time scales. © 2013 Moulay Rchid Sidi Ammi and Delfim F. M. Torres.